Natural Perylenequinone Compounds as Potent Inhibitors of Schistosoma mansoni Glutathione S-Transferase - Benson Otarigho; Mofolusho O. Falade (Life, 2023)
The existing treatment strategy for Schistosomiasis centers on praziquantel, a single drug, but its effectiveness is limited due to resistance and lack of preventive benefits. Thus, there is an urgent need for novel antischistosomal agents. Schistosoma glutathione S-transferase (GST) is an essential parasite enzyme, with a high potential for targeted drug discovery. In this study, we conducted a screening of compounds possessing antihelminth properties, focusing on their interaction with the Schistosoma mansoni glutathione S-transferase (SmGST) protein. We demonstrated the unique nature of SmGST in comparison to human GST. Evolutionary analysis indicated its close relationship with other parasitic worms, setting it apart from free-living worms such as C. elegans. Through an assessment of binding pockets and subsequent protein–ligand docking, we identified Scutiaquinone A and Scutiaquinone B, both naturally derived Perylenequinones, as robust binders to SmGST. These compounds have exhibited effectiveness against similar parasites and offer promising potential as antischistosomal agents.